2019
DOI: 10.7150/thno.29326
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic ternary nanohybrids for nonviral gene delivery of stem cells and applications on cancer therapy

Abstract: Cancer toxic agent-expressing mesenchymal stem cells (MSCs), which possess inherent tumor migration and penetration capabilities, have received increasing attention in cancer therapy. To ensure that this approach is successful, safe and efficient gene delivery methods for stem cell engineering must be developed. Methods : In this study, a magnetic ternary nanohybrid (MTN) system comprising biodegradable cationic materials, nucleic acids, and hyaluronic acid-decorated superparamagnetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 58 publications
0
22
0
Order By: Relevance
“…Results showed that the transfection efficiency increased from 20% to 65% under the magnetic field attraction. In vivo experiments in Cg-Foxn1nu/CrlNarl mice confirmed suppression of human glioma (U87MG) by magnetic ternary nanohybrid-transfected TRAIL-expressing hMSCs [ 391 ].…”
Section: An Overview Of Ion-mediated Transfection In Gene Editingmentioning
confidence: 99%
“…Results showed that the transfection efficiency increased from 20% to 65% under the magnetic field attraction. In vivo experiments in Cg-Foxn1nu/CrlNarl mice confirmed suppression of human glioma (U87MG) by magnetic ternary nanohybrid-transfected TRAIL-expressing hMSCs [ 391 ].…”
Section: An Overview Of Ion-mediated Transfection In Gene Editingmentioning
confidence: 99%
“…Furthermore, Huang et al developed a superparamagnetic iron oxide NPs decorated with hyaluronic acid and functionalized with TNFrelated apoptosis-inducing ligand (TRAIL) and CD44. The complex significantly decreases the tumor size and enhanced survival rate in the orthotopic xenograft cancer BALB/cAnN.Cg-Foxn1nu/CrlNarl mice model [102].…”
Section: Brain Tumor-targeted Gene Deliverymentioning
confidence: 96%
“…demonstrated that MSCs post gene transfection by using hyaluronic acid decorated SPIONs present a higher number of migrated cells at tumor sites when compared with none‐transfected MSCs. [ 30 ] However, this potential of IONPs seems is not universally workable for all cell types. For example, NeuroMag proved to have no impact on the migration of rat oligodendrocyte precursor cells.…”
Section: Challengesmentioning
confidence: 99%